Pregnancy as an important risk factor for the progression of diabetic retinopathy - Gurdak, Kinga; Kopczyńska, Urszula; Kopczyński, Cezary; Partyka, Aleksandra; Błaszczak, Ewa; Wójcik, Jakub; Dyrek, Martyna; Dydyk, Martyna; Malinowski, Piotr; Małachowski, Aleksander (Journal of Education, Health and Sport, 2024)
Diabetic retinopathy, also defined as diabetic eye disease is one of the main causes of eye complications and blindless in the world therefore leads to irreversible vision disorder and vision loss. A pregnant women as a patient is always a real challenge for doctors of various specialties. During this period, numerous systemic changes occur, such as increased blood pressure in the third trimester, increased blood volume insulin resistance with worsening glycemic control and excessive coagulation. The above complication may be reflected in the image of the fundus of the eye. Pregnancy may induce retinal disease such as diabetic retinopathy. This review article presents the incidence, pathogenesis and risk factors associated with diabetic retinopathy during pregnancy. More over in the following paper discussed management of diabetic retinopathy in pregnancy and guidelines are recommended based on the achievable evidence.